ZONES FOR EMPLOYMENT AND ECONOMIC DEVELOPMENT (ZEDE), AND THE IMPROVEMENT OF DISPOSSESSION MECHANISMS IN HONDURAS - Torres Sandí, Daniel (2020)
This article aims to assess the implications surrounding the Zones for Employment and Economic Development (zede), considering how its legal framework stands in front of Honduran institutions. Through the review of Honduran journals, official documentation, and statements from Human Rights organizations, we conclude that the project is steadilyongoing, despite widespread objections about its funding, legal implications, and posible effects on native population of the Honduras’ Caribbean shore.